Pendekatan Supervisi Direktif Sebagai Pembinaan dan Pengembangan Profesionalitas Guru - Zahrotur Roifah; Arum Wardatul Husna Asyauqiya; Binti Maunah; Hikmah Eva Trisnantari (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
Madrasah teachers play a strategic role in improving the quality of Islamic education, but in practice they still face challenges such as low professional competence, limited learning innovation, and a lack of effective and sustainable guidance. One effort to overcome these problems is through the implementation of targeted and systematic supervision. This study aims to analyze the concept and implementation of the directive supervision approach in madrasah teacher development and its implications for improving teacher professionalism. The directive approach is considered relevant because it provides clear, structured, and effective guidance to enhance teacher competence and performance continuously. This study uses the library research method with a descriptive qualitative approach, and data were obtained from books, scientific journals, and previous studies. The results show that directive supervision is effective in improving teacher professionalism through structured guidance, mentoring, and evaluation, enabling teachers to become more disciplined, skilled, and focused in carrying out their duties. However, if applied rigidly, this approach may limit teachers’ creativity and initiative. Therefore, directive supervision needs to be combined with collaborative elements so that teacher development becomes more adaptive, participatory, and sustainable.